Integration of Systems of the Exemplary Model Using Modern Tools of Industry 4.0 - Natalia DANIEL (Integracja systemów przykładowego modelu z wykorzystaniem nowoczesnych narzędzi Przemysłu 4.0, 2023)
Industry 4.0 is a common term that is constantly evolving. It involves the participation of different disciplines and areas of knowledge, as well as the integration of multiple technologies, both mature and emerging. Industry 4.0 defines things like the increase in demand for products that are customised. Personalisation goes hand in hand with differentiation in small batches, unique products and high production flexibility. That is why manufacturing companies use advanced technologies to accurately prepare for changes in global production. The authors aim to present an example of an integrated management system designed in line with “Industry 4.0” using the military sector as an instance. The developed integrated system combines: an ERP system, a CAD system, a PDM plug-in, an ERP Plus plug-in, a database system and a mobile application.
Keywords: Przemysł 4.0